Komparasi Kandungan Timbal (Pb) Kertas Bekas Mengandung Tinta Pasca Aplikasi Cairan Rumen Sapi Berdasarkan Lama Inkubasi - Annisa Rahmawati; Hesti Kurniahu; Sriwulan Sriwulan; Riska Andriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The addition of cow rumen fluid to waste containing cellulose can help decompose the cellulose contained in it through the composting process. Organic waste and paper waste containing ink are wastes that contain cellulose. However, the waste paper containing ink contains Lead (Pb) which is used as a color binding agent in the ink. In the composting process, in addition to the degradation process of organic components in paper, it is necessary to know the process of decreasing the Pb content in the compost material. This study was conducted with the aim of comparing the Pb content after application of cow rumen fluid on a mixture of used paper containing ink and organic waste for 60 days with used paper with ink for 7 days. The objects in this study consisted of two groups, the first group was used paper containing ink mixed with organic waste in a ratio of 1:1, then cow rumen fluid was added and incubated for 60 days, while the second group was inked waste paper added with cow rumen fluid and incubated for 7 days. Pb test incubation using AAS (Atomic Adsorption Spectrophotometer) method. The data were statistically tested by Independent T Test on SPSS 23 Software. The conclusions obtained from this study were the incubation time of inked paper waste with the addition of rumen fluid showed that the difference in Pb levels was not significant. The Pb content in both experimental groups was in accordance with the provisions of SNI 19-7030-2004.